Characterization of oil palm fronds hemicelluloses extracted by subcritical water extraction / Norsyabilah Ridzuan - Ridzuan, Norsyabilah (2015)
Oil palm plantations in Malaysia generate more than 36 million tonnes of pruned and felled oil palm fronds (OPF) and are generally considered as wastes. Fractionation of hemicelluloses from OPF using a hydrothermal process could be of interest in obtaining useable substrate for different product applications. The aim of this study was to optimize the subcritical water extraction (SWE) conditions of oil palm fronds on the hemicelluloses yield and consequently on the production of high molecular weight hemicelluloses (HMH) and low molecular weight hemicelluloses (LMH). In order to optimize the hemicelluloses yield, the effects of temperature (180-200°C), pressure (500-700 psi) and time (5-15 min) of SWE were examined applying three level Box Behnken design and response surface methodology (RSM). The liquid extract obtained at optimized conditions of subcritical water extraction was then precipitated with ethanol and filtered to produce high molecular weight hemicelluloses (solid precipitate). The supernatant was further separated using ultrafiltration lOkDa molecular weight cut off membrane to obtain low molecular weight hemicelluloses. All the samples were characterized for monosaccharides, xylooligosaccharides, lignin content, FTIR spectra and molecular weight determination. The statistical analysis indicated that three variables of SWE conditions had significant effects on the yields of hemicelluloses (p<0.05). The considered optimum conditions were: temperature of 185°C, pressure of 650 psi and contact time of 7 mins was 86.22%. Under these optimal conditions 16.64 mg/ml monosaccharides concentration of liquid extract, 7.86 mg/ml of HMH, 13. 72mg/ml ret en tate of LMH and 13.1 7mg/ml permeate of LMH were obtained. The monosaccharides composition of the liquid extract, HMH and LMH (retentate and permeate) contained xylose as major constituent followed by arabinose. This study demonstrated that the maximum yield of oil palm fronds hemicelluloses could be achieved by optimized the conditions of SWE through the RSM. The HMH and LMH separated via ultrafilltration membrane would be further investigated in the pharmaceutical and food applications